Singly versus Doubly Reduced Nickel Porphyrins for Proton Reduction: Experimental and Theoretical Evidence for a Homolytic Hydrogen‐Evolution Reaction. (30th March 2016) - Han, Yongzhen; Fang, Huayi; Jing, Huize; Sun, Huiling; Lei, Haitao; Lai, Wenzhen; Cao, Rui
Abstract: A nickel(II) porphyrin Ni‐P (P=porphyrin) bearing four meso ‐C6 F5 groups to improve solubility and activity was used to explore different hydrogen‐evolution‐reaction (HER) mechanisms. Doubly reduced Ni‐P ([Ni‐P ] 2− ) was involved in H2 production from acetic acid, whereas a singly reduced species ([Ni‐P ] − ) initiated HER with stronger trifluoroacetic acid (TFA). High activity and stability of Ni‐P were observed in catalysis, with a remarkable i c / i p value of 77 with TFA at a scan rate of 100 mV s −1 and 20 °C. Electrochemical, stopped‐flow, and theoretical studies indicated that a hydride species [H‐Ni‐P ] is formed by oxidative protonation of [Ni‐P ] − . Subsequent rapid bimetallic homolysis to give H2 and Ni‐P is probably involved in the catalytic cycle. HER cycling through this one‐electron‐reduction and homolysis mechanism has been proposed previously but rarely validated. The present results could thus have broad implications for the design of new exquisite cycles for H2 generation. Abstract : HER verstehen lernen : Doppelt und einfach reduzierte Nickelporphyrine mit vier meso ‐C6 F5 ‐Gruppen katalysieren die Wasserstoffentwicklung aus Essigsäure und Trifluoressigsäure über unterschiedliche Mechanismen. Experimentelle und theoretische Ergebnisse verweisen auf eine bimetallische Homolyse des Hydridintermediats, das durch oxidative Protonierung der einfach reduzierten Spezies gebildet wird.